2021
DOI: 10.1523/eneuro.0302-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

Noise in Neurons and Synapses Enables Reliable Associative Memory Storage in Local Cortical Circuits

Abstract: Neural networks in the brain can function reliably despite various sources of errors and noise present at every step of signal transmission. These sources include errors in the presynaptic inputs to the neurons, noise in synaptic transmission, and fluctuations in the neurons’ postsynaptic potentials (PSPs). Collectively they lead to errors in the neurons’ outputs which are, in turn, injected into the network. Does unreliable network activity hinder fundamental functions of the brain, such as learning and memor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 59 publications
1
3
0
Order By: Relevance
“…Our findings are closely related to the previous studies that reported the benefits of random neural noise ubiquitous in the cortex in memory recall and associative learning [Zhang et al, 2021, McDonnell and Ward, 2011]. For example, recent experiments showed that a high level of noise and randomness in the olfactory system (i.e., random and seemingly unstructured networks in the piriform cortex) allows for not only flexible encoding of sensory information but also maintenance of the encoded information [Caron et al, 2013, Pashkovski et al, 2020, Litwin-Kumar et al, 2017, Zhang et al, 2019].…”
Section: Discussionsupporting
confidence: 91%
“…Our findings are closely related to the previous studies that reported the benefits of random neural noise ubiquitous in the cortex in memory recall and associative learning [Zhang et al, 2021, McDonnell and Ward, 2011]. For example, recent experiments showed that a high level of noise and randomness in the olfactory system (i.e., random and seemingly unstructured networks in the piriform cortex) allows for not only flexible encoding of sensory information but also maintenance of the encoded information [Caron et al, 2013, Pashkovski et al, 2020, Litwin-Kumar et al, 2017, Zhang et al, 2019].…”
Section: Discussionsupporting
confidence: 91%
“…To execute SNNs on neuromorphic hardware, neurons and synapses must be mapped to their neuronal and synaptic circuits. However, the brain's neuronal circuit could be susceptible to faults from various sources, such as noise in synaptic transmission and fluctuations in post-synaptic potentials [12], eventually leading to errors in neuronal circuit outputs. Likewise, neural circuits in neuromorphic hardware may fail due to electrical interference and cross-talk between neurons [12] [13].…”
Section: Introductionmentioning
confidence: 99%
“…The opposing interpretation argues that movement variability is an exploratory behaviour, which allows for rich sensory input from the environment [4]. To ensure the reliability of neural networks, it is best to optimize errors and noise, which are unavoidable, and learn to retrieve motor memories in their constant presence [5]. Thus, rather than attempting to supress errors and noise, the brain learns to exploit them to reliably store memories [5].…”
Section: Introductionmentioning
confidence: 99%
“…To ensure the reliability of neural networks, it is best to optimize errors and noise, which are unavoidable, and learn to retrieve motor memories in their constant presence [5]. Thus, rather than attempting to supress errors and noise, the brain learns to exploit them to reliably store memories [5].…”
Section: Introductionmentioning
confidence: 99%